KEEFEKTIFAN PEMBELAJARAN DARING DI SEKOLAH DASAR MENURUT PESRSEPSI ORANG TUA - Anis Isrotul Ulla; Muslimin Ibrahim; Sri Hartatik; Pance Mariati (Universitas Negeri Medan, 2022)
Abstract: :Effectiveness of Online Learning Implementation in Elementary Schools According to Parents' Perceptions. This study aims to describe the perceptions of teachers and parents regarding the variety of online learning implementations in terms of what platforms are used and the effectiveness of online learning. The target of this study were parents from three elementary schools in the city of Surabaya, including SDN Rungkut Kidul I, SDN Rungkut Kidul II and SDI Wachid Hasyim. The method used by descriptive observational research was obtained by disseminating questionnaires. The results obtained in the study were during the implementation of online learning students using the Microsoft Teams and WhatsApp platforms. The effectiveness of online can be referred to the achievement of learning objectives that are in accordance with the basic competencies and grades obtained by students during online reaching above the minimum. The conclusion that can be drawn from this research is that online learning is fairly effective but pseudo, because the implementation of learning still has obstacles from the network, platform and conditions of each student. In addition, the learning outcomes obtained by students are not pure, aka there is help from parents or the internet. Keyword: Online Learning, Platforms, Parents. Abstrak: Keefektifan Pelaksanaan Pembelajaran Daring di Sekolah Dasar Menurut Persepsi Orang Tua. Penelitian ini bertujuan untuk mendeskripsikan persepsi guru dan orang tua terkait ragam pelaksanaan pembelajaran daring dilihat dari platform apa saja yang digunakan dan keefektifan pembelajaran daring. Sasaran penelitian ini adalah orang tua dari tiga Sekolah Dasar di Kota Surabaya, antara lain SDN Rungkut Kidul I, SDN Rungkut Kidul II dan SDI Wachid Hasyim. Metode yang digunakan penelitian observasional deskriptif, diperoleh dengan melakukan penyebaran angket. Hasil yang didapatkan dalam penelitian adalah selama pelaksanaan pembelajaran daring siswa menggunakan platform Microsoft Teams dan WhatsApp. Keefefktifan daring dapat dirujuk pada tercapainya tujuan pembelajaran yang sesuai kompetensi dasar dan nilai yang didapat siswa selama daring mencapi diatas minimum. Kesimpulan yang dapat diambil dari penelitin ini adalah pembelajaran daring terbilang efektif tapi semu, karena pelaksanaan pembelajaran masih terjadi kendala dari jaringan, platform maupun kondisi tiap siswa. Selain itu, hasil belajar yang didapat siswa tidak murni alias ada bantuan dari orang tua atau internet. Kata kunci : Pembelajaran daring, Platform, Orang Tua